If f(x) = 3x + 5 and g(x) = x – 1, then g[f(-3)] = ?

Question

If f(x) = 3x + 5 and g(x) = x – 1, then g[f(-3)] = ?

in progress 0
Natalia 2 weeks 2021-09-08T20:05:25+00:00 1 Answer 0

Answers ( )

    0
    2021-09-08T20:06:49+00:00

    Answer:

    -3fg

    Step-by-step explanation:

    I can’t tell exactly what you’re trying to say but if you’re trying to say:

    g x (f x (-3)), then here’s how you do it:

    g x (f x (-3))

    Multiplying a positive and a negative equals a negative: (+) x (-) = (-), then use the commutative property to reorder the terms.

    g x (-f x 3)

    g x (-3f)

    Multiplying a positive and a negative equals a negative: (+) x (-) = (-), the use the commutative property to reorder the terms.

    -g x 3f

    -3fg

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )